FRI0287 Proliferative nephritis forms in sle patients with minimal proteinuria and high sledai. (23rd January 2014) - Spinetto, M. A.; Pappalardo, C. M.; Vinicki, J. P.; Cruzat, V. C.; De Rosa, M.; Dubinsky, D.; Marini, A.; Nasswetter, G.
Abstract : Background: ACR and EULAR guidelines recommend performing renal biopsy in every SLE patient with proteinuria above 0, 5g/24h. Some patients show an active urine analysis with dysmorphic erythrocytes but proteinuria < 0, 5g/24h. Objectives: To analyzed clinical manifestations, SLEDAI and histological classes found in patients with SLE and proteinuria <0, 5g/24h without renal insufficiency Methods: Retrospective study of 33 adult patients with SLE (ACR 1997) and proteinuria <0, 5g/24h, were evaluated between 1995 and 2010 in the Division of Nephrology and Rheumatology at Clinical Hospital Jose San Martín. There were performed 192 biopsies, 35/192 (18%) had low proteinuria, but 2 were excluded due to renal insufficiency. We analyzed clinical manifestations and SLEDAI at the time of renal biopsy. All renal samples were studied by light microscopy and immunofluorescence and were classified according to the ISN RPS 2003. Data were analyzed using SPSS 17.0 program. Results: There were 25 women (76%) and 8 men (24%), average age of 34 years (19-65) IQR 17. Median of disease: 120 months (36-264) IQR 96. Cutaneous involvement was found in 28 patients (84.8%), arthritis in 21 (63.6%), hematological features in 17 (51.5%), serositis in 9 (27.3%), and no patient had neurological criteria. Anti DNA was positive in 24 patients (72.7%) and hypocomplementemia 20 (60.6%). Mean SLEDAI was 15 (DS 6.06). Conclusions: We found high prevalence of proliferative forms in SLE patients with low proteinuria (< 0, 5g/24h). As mean SLEDAI was high in this cohort, patients frequently required moderate/high steroids doses. We hypothesized that the absence of mesangial forms and low proteinuria were probably related to this fact. These findings could suggest renal biopsy in lupus patients with glomerular hematuria and proteinuria < 0, 5g/24h. SLEDAI is a tool that could be useful in the decision to perform renal biopsy. References: George K Bertsias et al, Joint European League Against Rheumatism and European Renal Association–European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations for the management of adult and paediatric lupus nephritis, Ann Rheum Dis 2012;71:1771–1782. Hahn BH et al, American College of Rheumatology guidelines for screening, treatment, and management of lupus nephritis, Arthritis Care Res 2012 Jun; 64(6):797-808. Sociedad Argentina de Reumatología y Sociedad Argentina de Nefrología, Primer Consenso Argentino sobre Diagnóstico y Tratamiento de la Nefropatía Lúpica, Rev Arg Reumatol. 2011; 22 (4): 06-37. Disclosure of Interest : None Declared